2016
DOI: 10.18632/oncotarget.12750
|View full text |Cite
|
Sign up to set email alerts
|

Risk of eighteen genome-wide association study-identified genetic variants for colorectal cancer and colorectal adenoma in Han Chinese

Abstract: BackgroundRecent genome-wide association studies (GWAS) identified eighteen single-nucleotide polymorphisms (SNPs) to be significantly associated with the risk of colorectal cancer (CRC). However, overall results of the following replications are inconsistent and little is known about whether these associations also exit in colorectal adenomas (CRA).MethodsThe SNP genotyping was performed using a Sequenom MassARRAY to investigate the association of these eighteen SNPs with colorectal neoplasm in a case-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 60 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…So far, two studies examined this association and they found significant associations of GRS with risk for advanced adenomas indeed 28, 29 , but both studies included only a subset of the currently known common genetic variants. Other researchers found meaningful associations between single SNPs and the risk for AA in different study populations 3032 . Nevertheless, one of those previous studies already found a stronger association of GRS with proximal neoplasms than distal neoplasms and hypothesized that – equivalent to germline mutations causing Lynch syndrome – many common genetic variants are also more closely related to neoplasms in the proximal colon compared to the distal colon 28 , a finding fully in line with our results.…”
Section: Discussionmentioning
confidence: 93%
“…So far, two studies examined this association and they found significant associations of GRS with risk for advanced adenomas indeed 28, 29 , but both studies included only a subset of the currently known common genetic variants. Other researchers found meaningful associations between single SNPs and the risk for AA in different study populations 3032 . Nevertheless, one of those previous studies already found a stronger association of GRS with proximal neoplasms than distal neoplasms and hypothesized that – equivalent to germline mutations causing Lynch syndrome – many common genetic variants are also more closely related to neoplasms in the proximal colon compared to the distal colon 28 , a finding fully in line with our results.…”
Section: Discussionmentioning
confidence: 93%
“…Rs7837328 – another polymorphism in CASC8 – was associated with pCa and CRC susceptibility. 7 , 15 Although the above studies have reported the association between polymorphisms in the CASC8 gene and risks of cancer, the results were not consistent. Thus, the effect of polymorphisms in the CASC8 gene on cancer is still unclear.…”
Section: Introductionmentioning
confidence: 84%
“…The single-nucleotide polymorphism (SNP) of rs10505477 – located in the intron of the lncRNA of CASC8 gene – had an intimate correlation with CRC susceptibility,1113 the risk of lung cancer, the prognosis for gastric cancer,14,6 and so on. Rs7837328 – another polymorphism in CASC8 – was associated with pCa and CRC susceptibility 7,15. Although the above studies have reported the association between polymorphisms in the CASC8 gene and risks of cancer, the results were not consistent.…”
Section: Introductionmentioning
confidence: 89%
“…Until recently, at least 6 independent case-control association studies have been conducted to investigate the association between rs4939827 and CRC risk in Chinese population. Three studies reported positive association results [ 15 , 19 20 ], and another three studies reported negative association results [ 21 23 ]. Until recently, three meta-analysis studies have been conducted [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%